PRE-DESIGN OF PRODUCTION TECHNOLOGY FOR GOTU KOLA LEAVES (CENTELLA ASIATICA) THROUGH A SPRINKLER IRRIGATION SYSTEM AS AN INGREDIENT FOR MAKING CAPSULES AND OINTMENTS - Adawiyyah Swasana, Nabila
Gotu kola (Centella asiatica) is a medicinal plant that has long been used in traditional medicine in various Asian countries. This plant has many health benefits, including increasing endurance, treating skin disorders, improving blood circulation, and improving cognition. Secondary metabolites such as asiaticoside and madecasoside contained in gotu kola function as anti-inflammatory, antioxidant, anti-cancer and neuroprotective. Market demand for gotu kola continues to increase, driven by the traditional medicine, food supplement, pharmaceutical and cosmetic industries. Gotu kola production on 1 hectare of land can reach 6.94 tonnes of wet biomass and 1.85 tonnes of dry biomass. The need for fresh ingredients for gotu kola reaches 5760 kg per year, and the number of products containing gotu kola continues to increase, with the need for simplicia reaching 126 tons per year. The pre-designed production system for capsules and ointments made from gotu kola leaves uses alternative innovations in the form of growing media engineering, namely the use of cow manure, 2 gram NPK fertilizer/plant, and 20 mL L-1 PGPR which is integrated with a sprinkler irrigation system. The land area used is 3000 m2 and is divided into 2 plots, namely the gotu kola biomass production plot and the post-harvest plot. The land for the gotu kola biomass production plot is 2500 m2. The total number of flat beds is 25 beds with a distance between beds of 1 m. Each bed has 4 rows of polybags with the number of polybags per row totaling 200 polybags. So the total effective area used in the cultivation system is 1250 m2. Apart from that, there is a post-harvest area which is used as a subsystem for drying harvested leaves and packaging. The post-harvest area is 500 m2 with a drying subsystem of 196 m2 which contains a drying oven. After the leaves are dried, the dried leaves are then supplied to a packaging subsystem which has an area of 304 m2. In this room, the dried leaves are ground and then packed into size 1 capsules in a packaging machine and put into bottles containing 100 capsules. Half of the milled product is processed into ointment with a net weight of filling per bottle of 10 grams. The location of this business is carried out on land in Cibodas village, Lembang sub-district, West Bandung Regency, West Java Province, at coordinates 6°58'50”S and 107°45'40”E at an altitude of 661 meters above sea level. This place was chosen because the altitude and temperature of this land are suitable for cultivating gotu kola so that it can produce optimal biomass. The selling price set for capsule sales is IDR 51,500 so that the sales BEP can be achieved when 768 units of capsules are sold, while the sales price set for ointments is IDR 46,500 so that sales BEP for ointments can be achieved when 4809 units are sold. This pre-design requires raw material costs of IDR 173,474,734 with total fixed costs per year of IDR 260,658,240 and total variable costs per year of IDR 206,124,688. The investment costs that must be incurred at the start of the business are IDR 445,121,334. Furthermore, investment costs will be returned within 1 year, 6 months and 3 days based on calculations carried out using payback period analysis. Business in the first 3 years can be said to be normal and feasible to run. This is because the NPV value with a bank interest rate of 6% shows a result of more than 1, namely IDR 393,897,905. A comparison between positive NPV and negative NPV also shows a value of 1.855 which shows the business is worth running. The Internal Rate of Return (IRR) value also shows a figure that is greater than the Minimum Attractive Rate of Return (MARR), namely 47.59%, which shows that the benefits obtained from this business are greater than the costs incurred. This business is still able to run normally even though there has been a decrease in revenue and an increase in raw material prices of 5 to 10%. These indicators show that the gotu kola ointment and capsule business is feasible to run.